Analysis of Village Budgeting from the Perspective of Regulations and Village Financial Governance: A Study of Ambarketawang Village, Gamping, Sleman, Fiscal Year 2025 - Ajeng Mutiara Sholihah; Ruti, Amanda; Nikita Ardesty; Shelly Merlia Listiani (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
Village budgeting plays a strategic role in ensuring effective, transparent, and accountable financial management at the local government level. This study aims to analyze village budgeting from the perspective of regulations and financial governance, focusing on Kalurahan Ambarketawang, Gamping, Sleman in the 2025 fiscal year. The research employs a descriptive qualitative approach using primary data from interviews with village officials and secondary data from official documents such as APBKal, RPJMKal, and related regulations. The findings indicate that the budgeting process in Kalurahan Ambarketawang generally complies with prevailing regulations and reflects good governance principles, including transparency, accountability, and community participation. This is evidenced by the high realization rate of budget absorption, which reached more than 90%, and the successful implementation of best practices such as participatory planning through community forums, the use of digital financial systems, and multi-channel transparency mechanisms. However, several challenges remain, particularly related to coordination, certainty of budget information, and human resource capacity. The study implies that strengthening institutional coordination, improving information systems, and enhancing the competence of village apparatus are essential to optimize village financial governance and ensure sustainable development outcomes.